A new species of the genus Tephriopis Hampson, 1926 (Lepidoptera, Erebidae) from China - Qi, Wen; Wang, Min; Wang, Houshuai (Zootaxa, 2026)
A new species of the genus Tephriopis Hampson, 1926, T. paradivulsa Qi, M. Wang & H. Wang sp. nov., was discovered from South and Southwest China. Illustrations of adults, wing venation and genitalia are provided for the new species. The type specimens were deposited in the Insect Collection of Department of Entomology, College of Plant Protection, South China Agricultural University, Guangzhou, China.